2017
DOI: 10.26719/2017.23.5.335
|View full text |Cite
|
Sign up to set email alerts
|

Mediator role of experiential avoidance in relationship of perceived stress and alexithymia with mental health

Abstract: Rôle de médiation de l'évitement expérientiel dans le rapport entre stress perçu, alexithymie et santé mentale RÉSUMÉ La présente étude transversale a examiné le rôle de médiation de l'évitement expérientiel dans le rapport entre le stress perçu, l'alexithymie et la santé mentale. Nous avons inscrit dans cette étude 440 étudiants (âge compris entre 18 et 30 ans) de l'Université des Sciences médicales de Kermanshah par la méthode d'échantillonnage aléatoire stratifié. Les instruments utilisés dans l'étude étaie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…Previously, in a study, the role of mediating variables such as experiential avoidance in the relationship between stress and mental health problems has been confirmed. 34…”
Section: Discussionmentioning
confidence: 99%
“…Previously, in a study, the role of mediating variables such as experiential avoidance in the relationship between stress and mental health problems has been confirmed. 34…”
Section: Discussionmentioning
confidence: 99%
“…The experiential avoidance can be a risk factor for a range of mental disorders, such as depression, somatic disorders, anxiety, and insomnia. 14 Experiential avoidance means avoiding unwanted or undesirable thoughts/ feelings. In other words, experiential avoidance means not being willing to accept inner feelings and thoughts.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, experiential avoidance means not being willing to accept inner feelings and thoughts. 14 In a study done by Smith, it was concluded that experiential avoidance led to psychological damages, including substance abuse, obsessive-compulsive disorder, panic disorder, borderline personality disorder, and post-traumatic stress. 15 In addition, research shows that emotional disorders and sleep disorders are related.…”
Section: Introductionmentioning
confidence: 99%
“…According to the accounts of experiential avoidance, alexithymia is being considered as a learned tendency to use maladaptive coping to deal with severe stress 98,99 . It is proposed that this tendency in alexithymics may relate to an unwillingness to tolerate aversive sensations, emotions, thoughts, and memories by altering the form or frequency with which they confront these unwanted experiences 32,100 . Additionally, this learned tendency is reinforced and maintained by giving immediate relief and down-regulating distress for threatening situations 32,101,102 , however, it is ultimately associated with the accumulation and intensi cation of unwanted emotions 103 .…”
Section: Discussionmentioning
confidence: 99%
“…Alexithymia is a multi-faceted personality trait involving di culty in identifying and expressing feelings, and an externally oriented thinking style; 28,29 it has been associated with stress-related disorders, including anxiety, post-traumatic stress symptoms (PTSS), and depression [30][31][32] . According to the stressalexithymia hypothesis, the inability of emotional awareness in alexithymics may lead to maladaptive responses when encountering with stressors, in turn increasing susceptibility to mental problems 33 .…”
mentioning
confidence: 99%